The Effectiveness of Group Discussion Methods and Learning Media in Enhancing Students' Understanding in the Qur'anic Studies Course at STIT Palapa Nusantara - Karmani, M. Ali (AS-SABIQUN, 2025)
This study explored the effectiveness of the group discussion method and learning media in enhancing students' understanding of the Qur'anic Studies course at STIT Palapa Nusantara. A quasi-experimental design was applied, with students divided into two groups: an experimental group that participated in group discussions supported by learning media, and a control group that followed traditional lecture-based instruction. The data were collected through pre- and post-tests. The data were analyzed using both descriptive and inferential statistics, with paired sample t-tests applied to compare pre- and post-test scores. Qualitative data were analyzed through thematic analysis, identifying key themes related to student engagement, learning collaboration, and retention. The results showed that the experimental group experienced significant improvement in their understanding, with mean scores increasing by 25 points, compared to a 7-point increase in the control group. Qualitative findings highlighted several benefits, including active student engagement, collaborative learning, and enhanced retention, all facilitated by the group discussion method and learning media. The study demonstrated that integrating these approaches fostered a deeper understanding of the material, promoted critical thinking, and improved retention. These findings provide valuable insights into how teaching strategies in Islamic education can be enhanced, emphasizing the importance of interactive and collaborative learning methods. This research contributes to the development of more effective teaching practices and provides evidence that combining group discussions with media-based learning is a promising approach for improving student outcomes in Qur'anic Studies.